INTERGRATION OF SIMULATION-BASED LEARNING IN THE NURSING PROGRAMME: A REFLECTION. - Liaw Sok Ying (Singapore Nursing Journal)
The use of simulation as an educational tool has increasingly received much attention in nursing education. This article describes the integration of simulation-based learning at all levels in a Bachelor of Science (Nursing) programme in a local university with the aims of deepening students' learning, integrating the clinical skills that students have learnt, facilitating the transition from classroom to clinical practice, and promoting patient safety in acute care.